Radiation Monitoring and Dose Estimation of the Fukushima Nuclear Accident 2013
DOI: 10.1007/978-4-431-54583-5_15
|View full text |Cite
|
Sign up to set email alerts
|

Source Term Estimation of 131I and 137Cs Discharged from the Fukushima Daiichi Nuclear Power Plant into the Atmosphere

Abstract: It is urgent to assess the radiological dose to the public resulting from the month-long discharge of radioactive materials into the atmosphere from the Fukushima Daiichi Nuclear Power Plant accident in Japan in March 2011. To do this task, computer simulations on the dispersion of radioactive materials in the environment are useful. However, the source term essential to computer simulations was not available. Thus, the Japan Atomic Energy Agency has been trying to estimate the source term of iodine and cesium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
6
0
3
Order By: Relevance
“…Emission data (emission rate and amount) was obtained from Katata et al . 8 and their earlier work 7 .…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Emission data (emission rate and amount) was obtained from Katata et al . 8 and their earlier work 7 .…”
Section: Methodsmentioning
confidence: 87%
“…The latest emission estimate of Katata et al . 8 (WSPEEDI-II) was compared to their earlier results 7 (WSPEEDI) to demonstrate the sensitivity of global results on the improved local scale deposition scheme used in WSPEEDI-II. Peak 131 I concentration results improved in all regions as the larger total emission of WSPEEDI-II reduced the general underestimation of concentrations ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recognized that there were several events of radioactive Cs release in the accident at FDNPP, and there was some extent of bias in the contribution of radioactive Cs from each reactor in these events [35][36][37]. Nishihara et al reported that the radioactive Cs in each reactor would be reflected in the variation of the 134 Cs/ 137 Cs activity ratio and the 135 Cs/ 137 Cs isotopic ratio [29], suggesting that the source of the radioactive Cs in the environmental samples could possibly be evaluated from the isotopic data such as the isotopic ratio and the activity ratio of radioactive Cs.…”
Section: Evaluation Of Contribution Of Radioactive Cs-2: Source Term mentioning
confidence: 99%
“…This makes it possible to carefully assess the risk to the population and take the necessary measures in advance to combat air pollution [13,15]. As a consequence, the development of methods for assessing the intensity of emissions of pollutants is of paramount importance for emergency assessment and response to the impact of hazardous substances accidentally released into the atmosphere as a result of accidents at industrial enterprises and nuclear power plants [1,9]. It is important to note that the estimation of emission rates is often an ill-posed problem for which there is no general method for solving, and each developed method solves the estimation problem taking into account certain simplifications in the system [2].…”
Section: Introductionmentioning
confidence: 99%